2014
DOI: 10.1016/j.jff.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of fucoxanthin isolated from Ishige okamurae against high-glucose induced oxidative stress in human umbilical vein endothelial cells and zebrafish model

Abstract: Available online A B S T R A C THigh glucose induced oxidative stress is implicated in intracellular toxicity in tissue and blood vessel such as oxidative stress, lipid peroxidation, and cell death. In this study, we attempted to investigate protective effects of fucoxanthin isolated from Ishige okamurae against high glucose induced oxidative stress in human umbilical vein endothelial cells (HUVEC) and zebrafish model. The ROS generation, lipid peroxidation and cell death were significantly reduced in both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Several studies have reported that among the pigments of brown algae, fucoxanthin can reduce oxidative stress and symptoms of metabolic syndrome via its anti-diabetic and anti-obesogenic effects [54,55,56,57]. In addition, Kang et al [58] reported that fucoxanthin isolated from IO can reduce high glucose-induced oxidative stress in human umbilical vein endothelial cells (HUVEC) and in zebrafish models. Taken together, the antioxidative effects of IO may be effective as supplementary treatment of metabolic syndrome, including obesity and diabetes.…”
Section: Composition Of Iomentioning
confidence: 99%
“…Several studies have reported that among the pigments of brown algae, fucoxanthin can reduce oxidative stress and symptoms of metabolic syndrome via its anti-diabetic and anti-obesogenic effects [54,55,56,57]. In addition, Kang et al [58] reported that fucoxanthin isolated from IO can reduce high glucose-induced oxidative stress in human umbilical vein endothelial cells (HUVEC) and in zebrafish models. Taken together, the antioxidative effects of IO may be effective as supplementary treatment of metabolic syndrome, including obesity and diabetes.…”
Section: Composition Of Iomentioning
confidence: 99%
“…Ishige okamurae is a brown seaweed widespread in South Korea throughout Japan to China. The ethanolic extract of I. okamurae has shown antioxidant, antidiabetes, antihypertension, and antiobesity effects [15,16,17]. Recent evidence reported that diphlorethohydroxycarmalol (DPHC) isolated from I. okamurae could efficiently induce apoptosis via downregulating Bcl-2 while activating Bax caspase-3 and caspase-9 in adipocyte cells [18].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data has suggested that the regular consumption of seaweeds can reduce the risk of developing diseases associated with oxidative stress. As a dietary antioxidant, fucoxanthin improves the antioxidant capacity of blood serum levels (Kang et al 2014), and is capable of quenching reactive oxygen species under hypoxic physiological conditions, unlike the majority of food-derived antioxidants (Kaneko et al 2013). Reactive oxygen species are known to cause cellular damage, which is implicated in the pathogenesis of disorders such as cardiovascular disease, cancer, metabolic syndrome, and type II diabetes.…”
Section: Introductionmentioning
confidence: 99%